The IMF Rice Liberalization Policy in Indonesia: The Case Study of Elite Behaviors in the Era of Gus Dur, Megawati, and SBY Government - Sunardi Purwaatmoko (Jurnal Borneo Administrator, 2022)
The research aimed to explain elite behaviour in Indonesia's political reform era. This research was based on primary data collected from unstructured interviews with respondents or samples and secondary data collected from library studies. In analyzing the data collected, descriptive and qualitative methods are applied. This research found that adopting the electoral system of the Proportional Multi-Member District and the lack of power and authority distribution from elite to interest groups tended to result in the emergence of small and pragmatic political parties trying to get constituent votes using political mobilization of the constituent voters. The emergence of political parties induces a patron-client relationship between the political candidate and his constituent voters through a broker-generating oligarchy within the party. For that reason, the policy-making process in the rice sector depends on the relative power of ideologist party coalitions and pragmatic party coalitions. The changes in rice policy depended on the political interaction between the old and pragmatic political oligarchy and the new and ideologist political oligarchy. The stronger the political coalition of the new political oligarchy consisting of new ideologists and reformist political parties, the more protective the rice policy will be, and vice versa. That is why we suggested that the election system should be changed into Single-Member District Electoral System to create a smaller number of political parties to avoid the emergence of pragmatic political parties. And interest groups should be strengthened to prevent the dominant power of the oligarchy.